Church, justice and liberation. The Church Social history the work of Jeffrey Klaiber S. J. - Cosamalón Aguilar, Jesús A. (2020)
One of the main concerns in the intellectual work of Jeffrey Klaiber S. J. is to what extent the internal characteristics of the Latin American and Peruvian Catholic Church were linked to the societies that professed this creed. The article examines this aspect in depth and states that Klaiber’s texts constitute a history of the Church “from below”. In this sense, the author points out that several interpretations of the Jesuit historian about the Latin American Church are permeated by categories of social history. In particular, the article highlights the complex relationship among the Church, societies, and the States from the colonial period to the 19th and 20th centuries, as well as the role of Catholic organizations’ advocacy for human rights in the final decades of the 20th century.